Enriching impact assessment at CIMMYT - La Rovere, R.; Dixon, John A.; Hellin, Jonathan (2008)
The International Center for Maize and Wheat Improvement (CIMMYT) is a CGIAR centre with a long tradition of impact assessment (IA). Until recently, such work had focused on the rates of adoption of improved germplasm and returns on investment. Limited attention was directed at measuring impacts in terms of livelihood security or poverty reduction. In 2005, therefore, CIMMYT's Impacts Targeting and Assessment Unit (ITAU) began to develop and promote more wide-ranging types of IA. In order to enhance its IA culture and institutionalize IA within the Center, ITAU organized a series of workshops that brought together different players amongst CIMMYT's staff and partners. Coupled with follow-up activities, these have made it possible for social and biophysical scientists and other partners to share their understanding of IA and their IA experiences. This brief describes the key elements of the process that led to the establishment of a learning platform for a CIMMYT-wide IA culture, as well as ways to consolidate achievements and progress on institutionalizing IA. It also states the lessons learned with regard to institutionalizing IA within the context of an international agricultural research centre.